1997
DOI: 10.1002/(sici)1097-0029(19970401)37:1<31::aid-jemt4>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative histology of pulmonary neuroendocrine cell system in mammalian lungs

Abstract: It is increasingly recognized that neuroepithelial endocrine cells and organoid clusters of these cells termed neuroepithelial bodies are widely distributed in the respiratory tract of vertebrates. This review focuses on the neuroepithelial endocrine system in the airway epithelium of mammals according to observations made in a wide range of species, as it appears in light and electron microscopy by means of various visualization techniques under normal and experimental conditions. Because there are similariti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…5‐Hydroxytryptamine (5‐HT) or serotonin has been implicated in a variety of physiological functions in the airways of humans and experimental animals. Serotonin within most mammalian airways, including humans, originates mainly from platelets and neuroendocrine cells (Lauweryns et al 1974; Scheuermann, 1997; Cazzola & Matera, 2000; Fu et al 2002). In the healthy airway of rodents, mast cells are the main source of serotonin (Weigand et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…5‐Hydroxytryptamine (5‐HT) or serotonin has been implicated in a variety of physiological functions in the airways of humans and experimental animals. Serotonin within most mammalian airways, including humans, originates mainly from platelets and neuroendocrine cells (Lauweryns et al 1974; Scheuermann, 1997; Cazzola & Matera, 2000; Fu et al 2002). In the healthy airway of rodents, mast cells are the main source of serotonin (Weigand et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The close localization of serotonin‐positive NEE cells with ciliary and mucous cells is highly indicative of some function of NEE cells. Serotonin induces mucus secretion in the digestive system of mammals (Menguy, 1967; Plaisancie et al ., 1998) and has been suggested to increase mucus secretion and ciliary beat frequency, as well as to be a potent vasoconstrictor in the respiratory system (Dey et al ., 1981; Adriaensen et al ., 1994a, 1994b; Scheuermann, 1997a, 1997b). Furthermore, immunocytochemical studies have revealed the colocalization of serotonin and neuropeptides in the same NEE cells, such as calcitonin (Adriaensen & Scheuermann, 1993), CGRP (Adriaensen & Scheuermann, 1993), SP (Adriaensen & Scheuermann, 1993), bombesin (Dayer et al ., 1985; Dey & Hoffpauir, 1986) and somatostatin (Dayer et al ., 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Several morphological studies indicate that the bioactive substances are released from the DCVs by exocytosis (for review, see Scheuermann 1987Scheuermann , 1997. Therefore, the position of the DCVs at the basal pole near the blood capillaries and in contact with the cell membrane suggests a potential release of their content into the circulation or into surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%